Spendception and AI-Driven Digital Payment Deception: A Literature Review - Fajar Susanto; Bhenu Artha; Sadath M. Nur; Felyanah Dessy Cinthya Putri; Cynta Akya Dinka (Fakultas Ekonomi, Universitas Ekasakti, 2026)
This systematic literature review examines